THE CENTER CONDITIONS FOR A CLASS OF CUBIC SYSTEMS - Dolichanin, Ć.; Romanovsky, V. G.; Stefanović, M. (Matematichki Bilten, 1996)
One of famous problems of the theory of Differential equations, namely, center-focus problem, are considered. For the cubic vector field \[ idwdt = w( 1-a_10w-a_01w -a_11ww -a_-13w^-1w^3 ), \] in the case when \(a_11 e -a_10a_01\) the necessary and some sufficient center conditions are obtained.